Development and Evaluation of a Tailored Pre-Professional Identity Workshop: A Case Study in Exercise Science - Kelly Clanchy; Clare Minahan; Elizabeth Cardell; Andrea Bialocerkowski (Journal of Teaching and Learning for Graduate Employability, 2022)
Pre-professional identity (PPI) aims to provide an understanding of, and connection to, the skills and knowledge contained in a degree and the intended profession of the student. Investigation into PPI is of importance to higher-education institutions as it provides a means of understanding a student’s orientation and motivation behind degree and career selection. Developing learning activities that capitalise on these motivations is proposed to increase student engagement, reduce attrition, and enhance employability. Using the growing, but relatively new profession of Exercise Science as an example, this study describes a workshop based on theoretical models relating to the concept of PPI, adult learning and self-reflective practices that can be integrated into programs to enhance students’ understanding of their professional identity. One hundred and seventy-three final year Exercise Science students participated in and evaluated the workshop. The workshop was evaluated using a theoretical framework specifically designed for the evaluation of training activities. The combination of the evaluation and feedback from students were synthesised to develop a model for the application of PPI activities across a three-year undergraduate degree.